An Exploratory Study of Salivary Calcitonin Gene‐Related Peptide Levels Relative to Acute Interventions and Preventative Treatment With OnabotulinumtoxinA in Chronic Migraine. Issue 2 (22nd October 2013) - Cady, Roger; Turner, Ira; Dexter, Kent; Beach, M. E.; Cady, Ryan; Durham, Paul
<x xml:space="preserve">Abstract</x> Objective To determine if baseline/interictal saliva calcitonin gene‐related peptide (CGRP) levels would be lower in subjects with chronic migraine receiving onabotulinumtoxinA compared with those receiving saline. Background CGRP is considered central to the pathogenesis of episodic migraine, but its relationship to chronic migraine is less understood. OnabotulinumtoxinA is an effective treatment for chronic migraine and has been demonstrated to inhibit the vesicular release of CGRP. Methods This was an exploratory, randomized, placebo‐controlled, crossover pilot study of 20 subjects that received onabotulinumtoxinA and saline injection (placebo). The amount of CGRP in saliva samples collected on a nonheadache or low headache day, and prior to and after treatment of a headache exacerbation was measured. Daily headache records, medications, and response to treatment were recorded in a diary. Results A decrease in baseline/interictal saliva CGRP levels for subjects receiving onabotulinumtoxinA from 39.4 ± 7.5 pg CGRP/mg total protein after the first month to 25.5 ± 4.1 pg after the third month was observed. However, this difference did not reach significance nor was it significant when compared to the saline treatment. There was a reduction in the number of headache days for both onabotulinumtoxinA and saline over baseline throughout the active phases of the study. However, there was no statistical difference in headache days between groups. Subjects with a greater than 50% response to onabotulinumtoxinA had better 2‐hour pain relief with acute treatment than non‐responders to onabotulinumtoxinA or saline. Conclusion While CGRP levels were not elevated during a migraine attack in chronic migraine subjects as has been reported in episodic migraine, there was an overall decrease in the baseline/interictal levels in response to onabotulinumtoxinA.